Functional Limitations and Physical Health in Community-Dwelling Medicare Advantage Beneficiaries: Variation by Race and Hispanic Subgroup. (December 2022) - Luck, Jeff; Govier, Diana; Ðoàn, Lan N.; Mahakalanda, Shyama; Zhang, Wei; Mendez-Luck, Carolyn
Objectives: The objective is to examine racial and ethnic heterogeneity in older adults' functional limitations and physical health.Methods: Data were from 2011 to 2015 Health Outcomes Survey of Medicare Advantage beneficiaries 65 and older ( N = 828, 946). Outcomes were Physical Component Summary (PCS) scores and need for assistance with activities of daily living (ADLs). Six non-Hispanic racial groups and five Hispanic subgroups were analyzed. Regression models adjusted for sociodemographic and health characteristics.Results: White and Asian respondents had the lowest unadjusted ADL difficulty rates and highest PCS scores. In adjusted analyses, Cuban respondents had the highest PCS scores and lowest rates of any ADL difficulty; White respondents had the lowest rates of specific ADL difficulties. Native Hawaiian or other Pacific Islander and multiple Hispanic respondents had the highest ADL difficulty rates.Discussion: Both the healthiest and highest need subgroups of Medicare Advantage beneficiaries were Hispanic. Understanding racial and ethnic subgroup differences may help target interventions to prevent or aid with functional limitations.